Mycelial growth of oyster mushroom in spawn made using different cereal grains, sawdust and vermiculite as substrate - UFITINEMA, Bonaventure; HAKIZIMANA, Modeste; NIYOMUGABO, Jean De Dieu (Mushroom Research, 2023)
Lack of sufficient and high-quality spawn are the problems that are affecting mushroom producers. To address this problem, this study was done to evaluate the effect of cereal grains, sawdust and vermiculite substrates on oyster mycelia growth in bottles. The experiment was conducted in Completely Randomized Design (CRD) where 6 different substrates (wheat, maize, rice and millet grains, sawdust and vermiculite all in bottles) were evaluated in a laboratory. Data was taken after every 2 days of inoculation until full colonization of substrates. The results showed that cereal grains (rice, millet, maize and wheat), sawdust, and vermiculite had a significant effect (P≤ 0.005) on oyster spawn mycelia growth. The substrates significantly (P≤ 0.005) influenced the mycelium running rate (growth) as observed on 2, 4, 6, 8, 10, 12 and 14 days after inoculation. Among all treatments used for oyster mushroom spawning, the results indicated that popcorn took the shortest time (approximately 9.4 days) to full colonization while rice was the second then followed by wheat at 10.3 and 13.1 days, respectively while vermiculite took 15 days to full colonization. Therefore, maize and rice grains are recommended to be used for oyster mushroom spawn.